Rare genital system tumours, neuroendocrine neoplasms: case series and literature review - Tolga Ciftpinar; Yuksel Ulu; Nilufer Cetinkaya Kocadal (Journal of the Pakistan Medical Association, 2025)
Neuroendocrine neoplasms (NENs) of the female genital tract are rare tumours. They behave more aggressively than other gynaecological cancers. Clinical presentation and treatment are not standard, and there is no specific guideline in place. Retrospective analysis of NENs of the female genital system was carried out between June 2020 and January 2024 in a tertiary care hospital. Twenty patients who had neuroendocrine morphology in histopathology were included in the study. Fourteen were diagnosed as NENs, whereas six were diagnosed as neuroendocrine differentiated tumours. Most of the cases had poor prognosis, and average survival was 14 months, 35 months, and 34 months, respectively. Half of the patients relapsed with metastases. Like neuroendocrine carcinomas, neuroendocrine differentiated tumours also had poor prognosis. NENs are diseases with poor prognosis and are diagnosed at advanced stage. This depends on multifactorial effects. Molecular and genetic research may be helpful to optimise the management of this heterogeneous tumour group. Keywords: Neuroendocrine neoplasm, Neuroendocrine differentiated tumour, Gynaecological neuroendocrine tumour.